Penerapan Akad Salam dalam Jual Beli Online di Marketplace Shopee - Herawati, Chika Putri (Sharia Faculty Islamic Economic Law Study Department, 2024)
In online buying and selling, a salam contract is a pre-order arrangement in which the buyer pays up front and the items are delivered at a later date and time. The payment system carried out in the application of the salam contract is at the beginning of the sale and purchase agreement which can be done through bank transfer, debit, COD (Cash On Delivery), minimarket, ShopeePay, and various other partners. This study employed a qualitative research methodology that using literature studies from a variety of sources, including books, journals, and student research findings in the form of theses and other similar works. Based on the Qur'an, Hadith, and Ijma, the study's findings indicate that the use of the salam contract in the Shopee marketplace is allowed as an economic activity because the transactions will be advantageous to both parties, which in this case are sellers and users. Users will get facilities that make it easier to find the items they want to buy, while sellers will be able to receive orders directly and send the goods.